Geology and Tectonics of Subduction Zones: A Tribute to Gaku Kimura 2018
DOI: 10.1130/2018.2534(04)
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional plate geometry and P-wave velocity models of the subduction zone in SW Japan: Implications for seismogenesis

Abstract: To accurately estimate the coseismic rupture area in a Nankai megathrust earthquake and predict seismic and tsunami hazards, various three-dimensional models of the subducting plate geometry and simple seismic velocity models of the subduction zone in SW Japan have been proposed. However, to ensure consistency among studies, more realistic and reliable standard models must be developed. Here, we use wide-angle ocean-bottom seismographic survey results to develop models of the three-dimensional geometry of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(78 citation statements)
references
References 0 publications
4
73
1
Order By: Relevance
“…The M7-class interplate earthquakes that were detected by the Japan Meteorological Agency since 1923 are indicated by the red stars. The iso-depths on the plate boundary (Nakanishi et al, 2018) are shown by the dashed purple contours (5-km interval). The black circles indicate the source distribution of shallow low-frequency tremor (Yamashita et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The M7-class interplate earthquakes that were detected by the Japan Meteorological Agency since 1923 are indicated by the red stars. The iso-depths on the plate boundary (Nakanishi et al, 2018) are shown by the dashed purple contours (5-km interval). The black circles indicate the source distribution of shallow low-frequency tremor (Yamashita et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The parameters of each subfault in the model are summarized in Table 1. The depth and dip angles of the subfaults were determined using a plate boundary model (Nakanishi et al, 2018) that was obtained by compiling the structural data from offshore surveys. The slip amount in the model, which was determined by a trial-and-error process during the tsunami simulations, was set to be larger at shallower depths.…”
Section: Revised Fault Model For the 1662 Hyuga-nada Earthquakementioning
confidence: 99%
“…c 2D plate geometry model (Kodaira et al 2000). d 3D plate geometry model (Nakanishi et al 2018). e Hypocenter distributions (Akuhara et al 2013) geometry models, the depth to the top of the plate is represented as lines connecting the plate depths (Fig.…”
Section: Converting Equal-interval Data To Kmlmentioning
confidence: 99%
“…The 250-m equal-interval data are provided in a vertical section beneath the user-specified profile for 3D seismic velocity models or in a rectangular parallelepiped under the user-specified search region for 3D plate geometry models. For 2D seismic velocity and Nakajima and Hasegawa (2007), the 3D plate geometry model from Nakanishi et al (2018), the 2D plate geometry and seismic velocity models from Kodaira et al (2006), and the hypocentral distribution from Akuhara et al (2013). The green rectangle on the Earth's surface shows the userdefined search area.…”
Section: Use Of 250-m Equal-interval Gridded Datamentioning
confidence: 99%
See 1 more Smart Citation